Hearing the voices of kinship foster carers in Northern Ireland: an inquiry into characteristics, needs and experiences. (30th July 2018) - Houston, Stan; Hayes, David; MacDonald, Mandi
Abstract : This study describes an investigation into the characteristics, needs and experiences of kinship foster carers in Northern Ireland. By adopting a mixed-methods approach with 54 carers, a number of salient themes was captured. The respondents were predominantly grandparents who experienced a significant incidence of health-related issues. The cohort also endured high levels of stress, particularly at the beginning stage of the foster placement. Consequently, their need for practical, emotional and respite support was most evident. In terms of the children for whom they cared, many required help at school, and some presented with challenging emotions and behaviours. Overall, these findings emphasised the importance of relationship-based social work and demonstration of accurate empathy to the carer.